Rhetorical Organisation of Risk Management Reports by Malaysian Banks - Khairul Firhan Yusob; Afida Mohamad Ali; Mei Yuit Chan; Geok Imm Lee (Proceedings, 2022)
Risk management reports (henceforth, RMRs) are paramount to an organisation’s business processes and are used to inform stakeholders on the current risks experienced by a company. Some reports by companies, such as banks, are receiving more attention due to their importance to the public and current economy. While a plethora of studies have been conducted on RMRs in other disciplines, such as business, accountancy and finance, the same scenario is not apparent in language studies. Therefore, the present study intends to linguistically analyse the RMRs published by Malaysian commercial banks by examining their rhetorical organisation. In doing so, 40 RMRs published between 2016 and 2020 were analysed for their rhetorical moves and steps. The findings recognised five rhetorical moves in the RMRs, of which one was optional, one was conventional, while the rest were obligatory. The present study could assist readers of RMRs to better understand the structure of the reports.